MEMBENTUK MASYARAKAT MANDIRI DENGAN MEMBANGUN ENERGI BIOMASSA - Agus Salim Harahap; Nursahara Pasaribu; Albert Pasaribu (Talenta Publisher, 2017)
Energy is a basic requirement for society. Currently the State of Indonesia is experiencing an energy crisis, lead to weakening economy of the State, It is proved by the high amount of energy imported gas reaching 58% of the total need of Domestic reached 6.1 million metric tons (MT). Indonesia has the potential of biomass energy source Its great according to US records. Commerce Department in its report: Renewable Energy Market Assessment Report: Indonesia, biomass energy sources that have been used as the only alternative source of 445 MW from the total existing sources amounting to 49.810 MW, The means 99% from the untapped sources of biomass. LPG gas is a basic requirement that the fundamental for a State to the smallest part of the countrynamely village / hamlet. where people need energy LPG gas in large quantities but low purchasing power. Currently the supply gas often deficient until the scarcity of fuel LPG gas. This condition is very difficult for the community to thrive. Biogas energy sources derived from biomass is abundant, but not many take advantage of its potential.biomass energy is very cheap, environmentally friendly, abundant resources, able to provide solutions for village communities and hamlets. With aerobic fermentation technology in the digester to produce biogas which can be helpful. Biogas can be used as fuel for cooking and electricity generation. Community dedication aims to Forming community will be self defense biogas energy. So that the villagers do not dependent So that citizens are not dependent on LPG gas are scarce and expensive price